Integrins in cancer stem cells - Gou, Siqi; Wu, Anqi; Luo, Zhigang (Frontiers in Cell and Developmental Biology, 2024)
Integrins are a class of adhesion receptors on cell membranes, consisting of α and β subunits. By binding to the extracellular matrix, integrins activate intracellular signaling pathways, participating in every step of cancer initiation and progression. Tumor stem cells possess self-renewal and self-differentiation abilities, along with strong tumorigenic potential. In this review, we discussed the role of integrins in cancer, with a focus on their impact on tumor stem cells and tumor stemness. This will aid in targeting tumor stem cells as a therapeutic approach, leading to the exploration of novel cancer treatment strategies.